Adiposity‐Independent Effects of Aging on Insulin Sensitivity and Clearance in Mice and Humans. Issue 3 (25th February 2019) - Ehrhardt, Nicole; Cui, Jinrui; Dagdeviren, Sezin; Saengnipanthkul, Suchaorn; Goodridge, Helen S.; Kim, Jason K.; Lantier, Louise; Guo, Xiuqing; Chen, Yii‐Der I.; Raffel, Leslie J.; Buchanan, Thomas A.; Hsueh, Willa A.; et al.
Abstract : Objective: Aging is associated with impaired insulin sensitivity and increased prevalence of type 2 diabetes. However, it remains unclear whether aging‐associated insulin resistance is due to increased adiposity or other age‐related factors. To address this question, the impact of aging on insulin sensitivity was investigated independently of changes in body composition. Methods: Cohorts of mice aged 4 to 8 months ("young") and 18 to 27 months ("aged") exhibiting similar body composition were characterized for glucose metabolism on chow and high‐fat diets. Insulin sensitivity was assessed by hyperinsulinemic‐euglycemic clamp analyses. The relationship between aging and insulin resistance in humans was investigated in 1, 250 nondiabetic Mexican Americans who underwent hyperinsulinemic‐euglycemic clamps. Results: In mice with similar body composition, age had no detrimental effect on plasma glucose and insulin levels. While aging did not diminish glucose tolerance, hyperinsulinemic‐euglycemic clamps demonstrated impaired insulin sensitivity and reduced insulin clearance in aged mice on chow and high‐fat diets. Consistent with results in the mouse, age remained an independent determinant of insulin resistance after adjustment for body composition in Mexican American males. Conclusions: This study demonstrates that in addition to altered body composition, adiposity‐independent mechanisms also contribute to aging‐associated insulin resistance in mice and humans.